Uji Akurasi Arah Kiblat Masjid Pondok Pesantren Sunan Drajat Kecamatan Paciran Kabupaten Lamongan Dengan Metode Mizwala Qibla Finder - Yasirul Amin; Sutopo Sutopo (JOSH: Journal of Sharia, 2022)
The mosque is one of the most important places for Muslims, one of which is the mosque at the Sunan Drajat Islamic Boarding School. The mosque is a place of worship for all Muslims, where one of the conditions and pillars that must be met is facing the Qibla, therefore further research is needed to determine the Qibla direction of the Sunan Drajat Islamic Boarding School Mosque. One of the measurement methods that can be applied is the Mizwala Qibla Finder Method. This study uses a field research method and the data collected includes general information about the Sunan Drajat Islamic Boarding School Mosque and the method of determining the Qibla direction of the mosque. Data collection techniques by observation, interviews, and study of documents sourced from the takmir of the mosque and mosque documents. Mizwala Qibla Finder is a modified instrument from sundial to istiwak stick which is used specifically to determine Qibla direction. Mizwala Qibla Finder uses the Theodolite concept, in other words, this tool is a miniature or transformation of the Theodolite as a tool to determine the Qibla direction with high accuracy. Based on the measurement results obtained, it can be concluded that the Qibla direction of the Sunan Drajat Islamic Boarding School Mosque is 294º1'. Meanwhile, when measurements were made using the Mizwala Qibla Finder method, there was an error in the direction of the Qibla by 2º-3º from the actual direction. This is because the initial method of measuring the Qibla direction was carried out using a very classical method, so that when the Qibla direction of the Mosque was tested using the Mizwala Qibla Finder, deviations were found, but still tolerable.